AKTIVITAS ANTIOKSIDAN DAN KOMPONEN BIOAKTIF KEONG IPONG-IPONG (Fasciolaria salmo) - . Nurjanah; Asadatun Abdullah; Azwin Apriandi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Ipong-ipong snail (Fasciolaria salmo) is one of sea water gastropods that have not been utilized optimally. People believe that the snail has the ef cacies for increasing stamina and vitality. However, scienti c data supporting the ef cacy of this snail has not been elucidated yet. The purposes of this research was determined the yield, chemical content (water, protein, fat, ash, acid insoluble ash and carbohydrates), bioactive components and antioxidant activity. The yield of shells, meat, and viscera were 69.69%, 22.08% and 8.22%, respectively. Watercontent, protein, fat, ash, acid insoluble ash and carbohydrates were 73.075%, 18.28%, 0.575%, 2.77%, 0.15% and 5.2%, respecitevely. Six bioactive components were detected i.e alkaloids, steroids, reducing sugars, carbohydrates, peptides and amino acids. Antioxidant activity using DPPH method obtained the result IC50 of the meat extract with chloroform, ethyl acetate and methanol solvent were 9210 ppm, 6825 ppm, 1513.8 ppm, respectively. Meanwhile for viscera extract were. 2825 ppm, 4600 ppm and 994,47 ppm, respectively.Keywords: antioxidants, bioactives, Fasciolaria salmo, proximate, yield.